Safety assessment of essential and toxic metals in infant formulas - Sipahi, Hande; Eken, Ayse; Aydin, Ahmet; Sahin, Gonul; Baydar, Terken (Turkish J Pediatrics, 2014)
The aim of this study was to assess toxic metal (Cd, Pb and Al) contamination and levels of three essential trace elements (Mn, Cr and Co) in 63 infant formulas. In addition, the levels of these metals in the study samples were compared with the acceptable limits of toxic heavy metals and the recommended daily allowances (RDAs) of essential trace elements. According to our results, the toxic metal levels measured in the formulas were within the acceptable limits, with the exception of Al levels in 8 of the 63 samples. In 16 samples, Mn levels exceeded 600 mu g/day, and the Cr content in 7 samples was higher than 5.5 mu g/day, these amounts being the adequate intake levels for infants. Cobalt levels in 10 formulas were higher than the RDA. In view of these findings, which indicate that metal levels in infant formulas are generally much higher than those found in breast milk, breast milk should be preferred for infant feeding. Moreover, since infants are potentially more susceptible to metals, infant foods should be monitored regularly and checked for contamination by toxic metals as well as for levels of essential trace elements.
Keywords: infant food; toxic metals; essential elements; provisional tolerable weekly intake (PTWI); recommended daily allowance (RDA); adequate intake